Computer-Assisted Instruction. (Education Digest, 1969)
Presents an interview with Patrick Suppes, head of the Institute for Mathematical Studies in the Social Sciences at Stanford University in California. Views of Suppes on the developments in computer-assisted instruction in U.S.; Proposals being developed for the adoption of computer-assisted instruction in the U.S. schools; Effort of schools at McComb, Mississippi, to have every student in grades 1 to 6 at a computer terminal for five to 10 minutes every day for intensive supplementary practice on mathematical problems.